Effect of short-term use of Glucocorticoids on skeletal muscle strength and endurance - Goyal, S; Sandhu, JS; Shenoy, S (Journal of Institute of Medicine Nepal, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Background: The study was carried out to investigate the effect of short-term use of glucocorticoids on skeletal muscle strength and endurance. Methods: Pre test and post test experimental design was made. Twenty-four healthy university students participated in the study. Eight subjects were given Prednisolone 5 mg tablets, 1 tablet, once daily for 10 days and other eight subjects were given Betamethasone 1mg tablets, one tablet, once daily for 10 days. Eight subjects were given all-purpose flour as placebo. Pre test and post test peak force, average force and fatigue index of quadriceps in extension moment was computed. Results: Non-significant differences were found in all the above variables (p>0.05) in both Prednisolone and Betamethasone groups. Conclusion: Short-term use of glucocorticoids has no significant effect on isometric strength and endurance in skeletal muscle. Key words: Glucocorticoids, Peak force, Average force, Fatigue index. Journal of Institute of Medicine, April, 2008; 30:1 18-20 The full text of this paper is available from the Journal of Institute of Medicine website